2004
DOI: 10.1002/hc.20016
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, characterizations, and crystal structures of organotin(IV) chloride complexes with 4,4′‐bipyridine

Abstract: The organotin(IV) chlorides R n SnCl 4-n (n = 3, R = Ph, PhCH 2 , n-Bu; and n = 2, R = n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…[61]. The Sn-N bond lengths of 2.472 (2) and 2.467 (2) Å are slightly longer than the 2.402 (2) Å observed in the polymeric [Me 2 SnCl 2 (4,4-bipy)] n complex [62]. All Sn-C bond lengths in the title compound almost are identical, and they are in the typical range of such bonds lengths found in diorganotin(IV) complexes.…”
Section: Single-crystal X-ray Analysesmentioning
confidence: 74%
“…[61]. The Sn-N bond lengths of 2.472 (2) and 2.467 (2) Å are slightly longer than the 2.402 (2) Å observed in the polymeric [Me 2 SnCl 2 (4,4-bipy)] n complex [62]. All Sn-C bond lengths in the title compound almost are identical, and they are in the typical range of such bonds lengths found in diorganotin(IV) complexes.…”
Section: Single-crystal X-ray Analysesmentioning
confidence: 74%
“…For the 4,4 0 -bipyridine adducts of diorganotin dichlorides, see: Ma et al (2004); Ng (1998). For the dimethyltin di(isothiocyanate) adduct of 1,10-phenanthroline, see: Najafi et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…The organotin dihalides include dimethyltin dichloride (Ng, 1998), dibutyltin dichloride and dibenzyltin dichloride (Ma et al, 2004); no pseudohalides have been reported. The dimethyltin diisothiocyanate adduct similarly adopts a chain motif (Scheme I, Fig.…”
Section: Commentmentioning
confidence: 99%
“…The design and development of new structures of organotin (IV) compounds has been attributed to the Lewis acidity nature of tin (IV) center which can coordinate to a variety of O‐, N‐, Cl‐, or S‐donor ligands . Tin atom can exist as tetra‐, penta‐, hexa‐ and hepta‐coordinated or form fluxional stereochemical complexes, however, the penta‐ and hexa‐coordinated organotin (IV) adducts are more common among them. The penta‐coordinated organotin (IV) complexes usually exist as trigonal bipyramidal geometry while the hexa‐coordinated complexes often adopt approximately octahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the more stable complexes have lower activities, the compounds with the average Sn‐N bond lengths ˃ 2.39 Å usually show anti‐tumour activity. This implies that predissociation of N‐donor ligands may be an important step in the mode of action of these ligands which follow with subsequent formation of tin‐DNA complex . To further improve the features of such compounds, this research shifted towards the use of diaryl and dialkyltin dichlorides and diisothiocyanides as starting materials.…”
Section: Introductionmentioning
confidence: 99%